2009
DOI: 10.1111/j.1741-6787.2009.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of Nurses to Report Medication Administration Errors in Southern Taiwan: A Cross‐Sectional Survey

Abstract: Background: Underreporting of medication administering errors (MAEs) is a threat to the quality of nursing care. The reasons for MAEs are complex and vary by health professional and institution. Aims: The purpose of this study was to explore the prevalence of MAEs and the willingness of nurses to report them. Methods: A cross‐sectional study was conducted involving a survey of 14 medical surgical hospitals in southern Taiwan. Nurses voluntarily participated in this study. A structured questionnaire was compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
3
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 22 publications
2
26
3
4
Order By: Relevance
“…[4] In Taiwan, a study reported that 66.9% of the nurses had experienced MAEs. [34] Another study reported that the mean rate of MAEs among nurses in Iran was 19.5%. [35] The average number of MAEs reported by nurses in a study conducted in Jordan was 2.2.…”
Section: Discussionmentioning
confidence: 99%
“…[4] In Taiwan, a study reported that 66.9% of the nurses had experienced MAEs. [34] Another study reported that the mean rate of MAEs among nurses in Iran was 19.5%. [35] The average number of MAEs reported by nurses in a study conducted in Jordan was 2.2.…”
Section: Discussionmentioning
confidence: 99%
“…Medication administration errors (MAEs) refer to ''medication errors that occur during the process of administering a drug'' (Lin & Ma, 2009) or ''any deviation from administration procedures, policies and/or practices for medication administration'' (Drach-Zahavy & Pud, 2010). Errors in administration account for most medication errors (Haw, Dickens, & Stubbs, 2005), threaten patient safety, and increase hospital costs (Kohn, Corrigan, & Donaldson, 1999; Taiwan Joint Commission on Hospital Accreditation [TJCHA], 2013).…”
Section: Introductionmentioning
confidence: 98%
“…The Taiwan Patient Safety Reporting System, Taiwan's clearinghouse for official MAE statistics, identified 1,760 MAE events at 66 hospitals in 2005 and 59,745 events at 698 hospitals in 2012 (TJCHA, 2013). However, because nurses are reluctant to report MAE because of administrative obstacles and fears of blame or lawsuits (Lin & Ma, 2009), these statistics may be significantly lower than actual MAE incident numbers. A survey instrument that measures nurse reactions after an MAE may allow hospitals to not only identify the key obstacles to MAE reporting but also develop support programs to facilitate the nurse's adjustment and return to duty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses are often fatigued and stressed due to the heavy load of work and organizational factors which causes them to conduct errors (Lin & Ma, 2009). The staff highlighted that there are constant emergency cases and the staff and doctors are always on their feet; making them vulnerable to errors.…”
Section: Medical Errorsmentioning
confidence: 99%